Indigenous Communication Forms and Their Potential to Convey Food Security Messages in Rural Ethiopia. Issue 3 (December 2016) - Nigussie, Hagos
This article examines the use of indigenous communication forms to convey food security messages in chronically food-insecure areas of Irob and Gulomekeda districts in eastern Tigray, rural Ethiopia. The study findings showed that there are no explicitly designed rural food security communication strategies, but food security messages are communicated through frequent public meetings. However, respondents believed that public meetings are dominated by the views and interests of government officials and development agents, which rarely entertain peoples' needs. The findings also showed that indigenous communication forms are widely practised in eastern Tigray, which rural people distinguish as potential conduits to convey different messages. Development agents and food security experts also believed that these communication forms have the potential to mobilize communities and enable them to actively engage in food security programmes. Thus, the overall result of the study shows that despite the knowledge about the potential of indigenous communication forms to convey food security messages, development agents are not using them in food security programmes, which has resulted in low-level community participation in the food security programmes.